Analysis of grip specificity on force production in grapplers and its effect on bilateral deficit grip specificity and bilateral deficit in force production among grapplers - Escobar-Molina, Raquel; Cuevas-Laguna, Miguel; Chirosa-Ríos, Ignacio J.; Merino-Fernández, María; Chirosa-Ríos, Luis J.; Franchini, Emerson (Frontiers in sports and active living, 2023)
The use of strength training is important for athletes in combat sports such as judo and jiu-jitsu. Specificity is key when prescribing strength training programs for athletes, considering maximal strength, muscular power and strength-endurance. Grappling combat sports require grip control, which is necessary to execute throwing techniques and groundwork. The aim of this study was to verify the bilateral strength deficit in general and in grappling combat sport-specific action in the control group and grapplers. A sample of 73 subjects, divided into 2 groups, was used: the Student Group (15 females and 16 males) and the Grappler Group (29 males and 13 females). The male and female participants attended four laboratory sessions over a 48-hour interval, the first two to familiarize themselves with the Electromechanical Functional Dynamometer (EMFD), and the last two to collect maximal isometric strength data, using a standard grip and a judo/jiujitsu specific grip. Significant differences in mean and peak forces ( p < 0.001) were found, with high performance combat sport athletes having greater maximal isometric strength compared to students both bilaterally and unilaterally ( p < 0.001). All comparisons also indicated higher values for males compared to females ( p < 0.001). The results suggest that specific training in combat sports as well as sex differences play a significant role in maximal isometric strength performance. The type of grip used affects the application of force in the upper limb isometric strength tests, finding a main effect of grip type ( p < 0.001), with the standard grip obtaining higher levels. However, the dominance between hands remains constant. More research is needed on specific judogi/jiu-jitsu-gi grips and their impact on maximal isometric strength with the EMFD.